Out-of-hospital cardiac arrest in elderly individuals. (14th October 2021) - Qaderi, V; Ball, J; Nehme, Z; Neumann, J T; Wolfe, R; Woods, R; Tonkin, A M; Smith, K; McNeil, J J
Abstract: Background: Out-of-hospital cardiac arrest (OHCA) is associated with poor outcome, particularly in elderly people. Due to the shift in global demographics towards an ageing population, understanding risk factors for OHCA is essential for the development of primary prevention strategies. Thus, we aimed to identify predictors for OHCA in a large, community-dwelling cohort of elderly individuals. Methods: We analyzed data from 11, 156 participants enrolled in a randomized, placebo-controlled primary prevention trial, investigating the effect of low-dose aspirin in individuals aged 70 years or above. At baseline all participants had no prior cardiovascular disease events, dementia or major physical disability. OHCA events occurring within 5 years were identified by probabilistic data-linkage with a state-wide out-of-hospital cardiac arrest registry. Possible predictors included age, sex, anthropometric measures, conventional cardiovascular risk factors, renal function and frailty. To evaluate the association with OHCA, we performed univariable and multivariable Cox regression analyses. In exploratory analyses we also evaluated the effect of low-dose aspirin on OHCA events. Results: In the cohort 54.7% were female and median age was 74.1 years (Interquartile Range [IQR] 71.8–77.7). During a median follow up time of 4.7 years (IQR 3.4–6.0) we recorded 67 OHCA events with presumed cardiac cause. The incidence rate was 1.07 per 1, 000 person-years (95% Confidence-Interval [CI] 0.80–1.40). The mortality rate following OHCA was 91.2% (n=62). Univariable Cox regression analyses identified age, sex, weight, abdominal circumference, serum creatinine, diabetes, arterial hypertension, intake of antihypertensive medication and pre-frailty as predictors for the outcome. In multivariable Cox regression analyses we identified age (Hazard Ratio [HR] 1.06, CI 1.00–1.13), female sex (HR 0.49, CI 0.26–0.94) and pre-frailty (HR 1.92, CI 1.03–3.58) to be independent predictors (Table). In exploratory analyses there was no effect of low-dose aspirin on OHCA (HR 1.52, CI 0.87–2.70). Conclusion: In a large, contemporary cohort of healthy, elderly individuals we describe a significant incidence of OHCA events associated with a very high mortality. We identified age, sex and pre-frailty, but interestingly not conventional cardiovascular risk factors as independent predictors of OHCA. We could not show a benefit of low-dose aspirin treatment, although the number of events was small. Our findings emphasize the importance of preventive strategies for pre-frailty in elderly individuals. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The ASPREE study was primarily funded by the National Institute of Aging and National Cancer Institute at the National Institutes of Health (grant number U01AG029824), the Australian National Health & Medical Research Council (grants 334047 & 1127060), Monash University (Australia) and the Victorian Cancer Agency (Australia).